Optimizing simulation of deficient limb's strokes in freestyle for swimmers with unilateral transradial deficiency - Nakashima, M.; Takahashi, R.; Kishimoto, T. (Journal of Biomechanical Science and Engineering, 2020)
The present study focused on freestyle swimming by swimmers with unilateral transradial deficiency. It has not been clarified yet whether the deficient limb should move so as to match the tempo of the intact upper limb, or if it should move as fast as possible to produce thrust by itself. The objective of this study was to solve the theoretically ideal deficient limb`s strokes in freestyle for a swimmer with unilateral transradial deficiency by using the optimizing simulation. The method of the optimizing simulation of arm strokes considering muscle strength characteristics was developed in a previous study. This method was utilized to solve the deficient limbs` strokes in the present study. Actual swimming by a participant was reproduced by simulation first. Since the resultant swimming speed of the simulation was in the range of the experimental speed, the validity of the simulation was confirmed. Next, optimizing simulations were conducted for the case of maximum shoulder joint torque multiplied by 1.0, 0.85 and 0.72. From these results, a significant increase in the swimming speed was found for the optimized cases. It was also suggested that the contribution by the deficient limb to propulsion can be increased by up to 15% of the intact limb. The optimized stroke was found to have a later timing and faster motion than the original stroke. This motion was realized by the principle that more joint torque can be exhibited in adduction than in flexion when the joint angular velocity was high.